The students empowerment in the sMOOC - Gil Quintana, Javier; Martínez Pérez, Jorge (Revista Complutense de Educación, 2017)
The ECO European project (E-learning, communication, Open-Data) has contributed to dissemination of the MOOC throughout the European continent, therefore, proving the expansive development of these models of education that allow participation and interaction through social networks in the platform of the course. The special feature about this project is the student’s empowerment, which has been publicized as a proposal that allows the users to create their own sMOOC. In this study, we have analyzed this massive, open and online model course, describing the advantages and disadvantages of them, besides de formative and motivating factors that guide the students, not only to enroll in particular courses but also to request for their own space to be able to create a sMOOC. Basing on mixed methods, the educational environment has been investigated during two consecutive courses created by the Master Redes Sociales y Aprendizaje Digital from the UNED University, setting out the analysis of this new formative model and the subsequent creation of an innovative proposal around the sMOOC model. The study has been developed from spaces such as the communicative tools of the subject platform and the interactions shown in the groups created in Facebook. The interviews and annotations from the daily diary investigation, specified by the questionnaires. We will observe how the student’s empowerment is limited to multiple factors that impede an optimum development of these courses and we will value the academic training as one of the incentives that cause the desire of sharing the knowledge through the sMOOC, motivating an improvement of the quality of education, another way of understanding education and, undoubtedly, another way of understanding the current society.
Keywords: MOOC; elearning; higher education; open education